A DNAzyme-augmented bioorthogonal catalysis system for synergistic cancer therapy. Issue 26 (17th June 2022) - You, Yawen; Liu, Hao; Zhu, Jiawei; Wang, Yibo; Pu, Fang; Ren, Jinsong; Qu, Xiaogang
Abstract : A DNAzyme-augmented and tumor-targeted bioorthogonal catalysis system is constructed for synergistic cancer therapy. It promotes the generation of Cu(i ) and ROS using endogenous H2 O2, thereby achieving in situ drug synthesis and chemodynamic therapy. Abstract : As one of the representative bioorthogonal reactions, the copper-catalyzed click reaction provides a promising approach for in situ prodrug activation in cancer treatment. To solve the issue of inherent toxicity of Cu(i ), biocompatible heterogeneous copper nanoparticles (CuNPs) were developed for the Cu-catalyzed azide–alkyne cycloaddition (CuAAC) reaction. However, the unsatisfactory catalytic activity and off-target effect still hindered their application in biological systems. Herein, we constructed a DNAzyme-augmented and targeted bioorthogonal catalyst for synergistic cancer therapy. The system could present specificity to cancer cells and promote the generation of Cu(i ) via DNAzyme-induced value state conversion of DNA-templated ultrasmall CuNPs upon exposure to endogenous H2 O2, thereby leading to high catalytic activity for in situ drug synthesis. Meanwhile, DNAzyme could produce radical species to damage cancer cells. The synergy of in situ drug synthesis and chemodynamic therapy exhibited excellent anti-cancer effects and minimal side effects. The study offers a simple and novel avenue to develop highly efficient and safe bioorthogonal catalysts for biological applications.